PENDAMPINGAN LOMBA DRUMBAND DALAM KEGIATAN MBKM BELA NEGARA DI KOTA SALATIGA - Elisabeth, Esra; Siwi, Kristanjung Raka; Wulandari, Fitri; Setyawan, Rafli (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This Community Service Activity (PkM) aims to contribute by providing assistance and support for the city-level drum band competition in Salatiga at State Elementary School 03 Mangunsari. The PkM activity is carried out in two stages: the drum band training preparation phase and the drum band competition support phase. The drum band training preparation took place from September 4 to September 18, 2023, at the school, while the drum band competition support phase was conducted on September 23, 2023, at Kridanggo Stadium Salatiga. In the first phase, the author, together with the coach and teachers, assisted the training sessions for the competition participants in musical performance and dance movement formations. The authors also contributed to creating attributes and drum band equipment such as fans, flags, and others. In the second phase, the authors, along with the committee, organized the makeup and costumes for the competition participants, found a suitable area for the drum band participants around the stadium, provided refreshments, and actively accompanied the participants during the street parade. The activity was concluded with documentation to capture the success of the event. The authors suggest that the development of this activity can involve a broader scope, not limited to mere assistance but also incorporating drum band training. This step is taken considering that the authors have acquired previous knowledge and skills that can be applied to provide more structured and sustainable training.